The Urgency of Islamic Education In Improving Understanding The Tarjih Maslahah For Mafsadah In The Istinbat Of Islamic Law (Method Analysis Imam ‘Izzuddin Bin Abdussalam) - Mubarrak, Zahrul; Asmuni; Adly, Muhammad Amar (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research focuses on looking at the urgency of Islamic education in expanding understanding of maqashid sharia in the concept of ushul fiqh, Islamic education is important for expanding understanding of maslahah and mafsadah in legal istinbath methodology, and describes the methods proposed by Izzudin to resolve the contradiction between maslahah and sorry. This research includes qualitative research which is descriptive analysis with a logical and historical philosophical approach. The data collection technique used is library research. The primary source for this research refers to the book Qawaid al-Ahkam fi Masalih al-Anam and the book Syajarat al-Ma'arif wa al-Ahwal wa Salih al-Aqwal wa al-A'mal. These findings explain that the concepts of maslahah and mafsadah in Islamic law will become more optimal if their understanding is strengthened and disseminated through Islamic education, especially those closely related to maqashid sharia. Maslahah supports the objectives of sharia in kulliyah khamsah, while mafsadah contradicts it. Proposals to reconstruct maqashid sharia independently of kulliyah khamsah were rejected because they usually only combined or complemented existing principles. Maslahah and mafsadah are important elements in Islamic legal istinbath, and must be managed within the framework of sharia dhawabith to avoid subjectivity and legal instability. Izzudin offers four methods to resolve the contradiction between maslahah and mafsadah, namely jam'u (merging), tarjih (weighing), takhyir (selection), or tawaqquf (termination). He emphasized that the contradiction between these two concepts is often only relative and depends on perspective, suggesting to assess the dominance of one aspect over the other in a given situation. This will of course be more optimal if it is conveyed and emphasized through the participation of Islamic education, so that discussions related to tarjih maslahah on mafsadah, especially in the study of Islamic law will become more interesting and developed.